2021
DOI: 10.1108/jec-03-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Family across borders social capital and diaspora entrepreneurial preparedness

Abstract: Purpose The purpose of this paper is to study the way in which family ties influence the entrepreneurial preparedness of the diaspora family business owner. Design/methodology/approach In-depth interviews were carried out with 15 Cypriot family business owners hosted in various countries. The paper draws on social capital theory and uses an abductive analytical approach. Findings The findings of this paper illustrate that family ties coming from the family across borders play a significant role for diaspor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 110 publications
0
15
0
Order By: Relevance
“…The multiple geographical locations might allow migrants to live, work and obtain necessary resources from and through family (Bagwell, 2015) and pursue business opportunities sequentially or even in parallel (Elo et al , 2019; Drori et al , 2009). The migrant’s family plays a role in granting migrant entrepreneurs access to these resources, not only in the country of residence and origin (Karayianni et al , 2021; Li and Johansen, 2021) but also in other countries where migrants have kinship connections (Bagwell, 2015; Bagwell, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The multiple geographical locations might allow migrants to live, work and obtain necessary resources from and through family (Bagwell, 2015) and pursue business opportunities sequentially or even in parallel (Elo et al , 2019; Drori et al , 2009). The migrant’s family plays a role in granting migrant entrepreneurs access to these resources, not only in the country of residence and origin (Karayianni et al , 2021; Li and Johansen, 2021) but also in other countries where migrants have kinship connections (Bagwell, 2015; Bagwell, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The second article, “Family across borders social capital and diaspora entrepreneurial preparedness” by Karayianni et al (2021), studies the influences of family ties on the entrepreneurial preparedness of the Cypriot diaspora family business owners in Australia, South Africa, the UK and the USA. Their results show that family ties across borders play an important role in diaspora family business owners’ entrepreneurial preparedness.…”
Section: The Articles In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The economic influence of diaspora on international entrepreneurship patterns is well documented (Karayianni, Hadjielieas, & Glyptis, 2021). This is due to the need for multiple stakeholders to collaborate on joint projects using embedded network relationships (Jafari-Sadeghi, Nkongolo-Bakenda, Anderson, & Dana, 2019).…”
Section: Diaspora and International Entrepreneurshipmentioning
confidence: 99%
“…Moreover, it has been observed that cash flow management for family firms has not been easy, especially after the outbreak of the deadly disease, COVID-19, around the world (Kraus et al, 2020;Ward, 2020). Critical scrutiny of the available family business studies reveals that many recent studies are done from corporate governance and succession planning perspectives (Ferrari, 2021;Karayianni, Hadjielias, & Glyptis, 2021;Udomkit, Kittidusadee, & Schreier, 2021;Wu, Coleman, Rahaman, & Edziah, 2020;Yu-Thompson, Lu-Andrews, & Fu, 2016). Shockingly, according to the researchers' best knowledge, meager scholarly attention has been observed when it comes to financial management challenges faced by family businesses.…”
Section: Introductionmentioning
confidence: 99%